Genetic Insights into Bicuspid Aortic Valve Formation - Brigitte Laforest; Mona Nemer (Cardiology Research and Practice)
Bicuspid aortic valve (BAV) is the most common congenital heart defect, affecting 1-2% of the population. It is generally diagnosed late in adulthood when deterioration of the abnormal leaflet becomes clinically evident. BAV patients have an increased risk of developing serious complications, including stenosis, regurgitation, endocarditis, dilation of the aorta, aortic dissection, and aneurysm. BAV is a heritable trait, but the genetic basis underlying this cardiac malformation remains poorly understood. In the last decade, thanks to studies in animal models as well as genetic and biochemical approaches, a large number of genes that play important roles in heart development have been identified. These discoveries provided valuable insight into cardiac morphogenesis and uncovered congenital-heart-disease-causing genes. This paper will summarize the current knowledge of valve morphogenesis as well as our current understanding of the genetic pathways involved in BAV formation. The impact of these advances on human health including diagnosis of BAV and prevention of cardiovascular complications in individuals with BAV or with a family history of BAV is also discussed.